Penerapan Project Based Learning untuk Melatih Kemampuan Literasi Tumbuhan Abad 21 pada Siswa SMA - Rizkamariana, Febby; Diana, Sariwulan; Wulan, Ana Ratna (Assimilation: Indonesian Journal of Biology Education, 2019)
This study aims to analyze the implementation of project based learning (PjBL) in improving high school students’ ability of 21st century botanical literacy. This study used quasi experimental method through non-equivalent control grup design. In the design of this study, there was a pre-test about botanical literacy before the treatment in experiment class and control, then it was done a treatment in experiment class with PjBL model and traditional learning in control class. After that, the students were given post-test about botanical literacy after learning activities. Sample in this study as much as 2 classes that belongs to class ten in one of High School in Cimahi City. The determination of study sample was conducted with purposive sampling technique because in choosing sample considering the condition of the students who have not learned yet about plants classification in school. Botanical literacy that was measured in this research is the ability to think critically to classify plants and solve the problem about plants. The result of the research is average of N-gain in the experimental class increased with moderate category, in the average of N-gain in the control class increased in low category. Overall, the activities in the stage of PjBL model has finished well by the teacher and students. Almost all the students agree that PjBL model give chances to the students to apply the knowledge on classifying plants, train on solving problem, and improve the learning motivation.